Safety and tolerability of exenatide twice daily in patients with type 2 diabetes: integrated analysis of 5594 patients from 19 placebo-controlled and comparator-controlled clinical trials - MacConell, Leigh (Dove Medical Press, 2012)
BACKGROUND: Exenatide twice daily is a first-in-class glucagon-like peptide receptor agonist approved for the treatment of type 2 diabetes. The objective of this analysis was to evaluate the safety profile of exenatide twice daily and to compare its profile with that of a pooled comparator (placebo and insulin) in patients with type 2 diabetes. METHODS: Data from 19 completed, randomized, controlled clinical trials of exenatide twice daily (5 μg and 10 μg) were pooled and analyzed; the pooled data included 5594 intent-to-treat patients who were followed for 12–52 weeks. Incidence rates, exposure-adjusted incidence rates, and 95% confidence intervals around risk differences between groups were calculated. RESULTS: Baseline demographics and exposure time were comparable between groups (exenatide, N = 3261; pooled comparator, N = 2333; mean exposure time 166–171 days). Transient, mild- to-moderate nausea was the most frequent adverse event with exenatide (36.9% versus 8.3% in the pooled comparator). The incidence of hypoglycemia (minor or major) with concomitant sulfonylurea (exenatide 26.5%, pooled comparator 20.7%) was higher than that without sulfonylurea (exenatide 3.1%, pooled comparator 2.7%) in all groups. Serious adverse events, discontinuations due to serious adverse events, and deaths were reported with similar frequency in the exenatide and pooled comparator groups. Composite exposure-adjusted incidence rates were not statistically different between groups for pancreatitis, renal impairment, or major adverse cardiac events; there was a difference in incidence rates for benign thyroid neoplasm (0.3% versus 0%). CONCLUSION: Overall, this analysis, representing over 1500 patient-years of exposure, demonstrated that exenatide twice daily was safe and generally well tolerated in patients with type 2 diabetes. The incidence of most adverse events, including serious adverse events, was similar in both exenatide-treated and comparator-treated patients. The most distinct differences between groups were in gastrointestinal-related adverse events, which is consistent with other therapies within the glucagon-like peptide class.